Re-framing ‘counterfeit from a public health perspective’: A case for fraudulent medicine - Bandiera, Rhiannon (The Australian and New Zealand journal of criminology, 2017)
‘Black market’ counterfeiters operating outside of authorised industry are often framed as the perpetrators of dangerous and defective medicines within legal pharmaceutical markets. However, the assumption that all medicines which deliberately violate regulatory standards and quality specifications have black market origins is ill conceived, as poor medicine quality can occur regardless of who the manufacturer of the medicine may be. This paper proposes a reframing of all pharmaceutical products which intentionally, or negligently, fail to comply with regulatory standards and which are then fraudulently depicted as being of standard, from ‘counterfeit’ to ‘fraudulent medicines’. This proposal is reinforced with examples from Australian law, where Australian pharmaceutical companies, who deliberately violated regulatory standards and produced defective and dangerous medicines, have been prosecuted using legislation designed to capture poor-quality counterfeit drugs. The paper argues that these corporate crimes should not be framed as ‘counterfeiting’ but as ‘frauds’, thus containing acts of ‘counterfeiting’ to existing intellectual property law and providing due recognition for all acts which defraud and cause harm to the consumer.